Decision-making among diverse interests: the use of future scenarios in local forest management policy, a proposed methodology - Wollenberg, Eva Karoline (1998)
The purpose of this concept paper is to propose a methodology for enchancing the policy-making process in local forest management (LFM). Local forest management is defined here as the involvement of people living near a forest in activities intended to maintain or enhance the forest and improve local people's well-being. As an umbrella concept, LFM included the rehabilitation of forests on degraded lands, management of natural forest, intensification of agroforestry to reduce pressure for use of natural forest, logging by communities, the sharing of management responsibilities with the state (co-management), nurseries, hunting and gathering by so-called traditional populations and wage employment for local people planting trees. It covers both development interventions as well as indigeneous practices. This paper explores the potential of a future scenario method for improving the policy-making process. The emphasis of the method is on the process of generating future scenarios through stakeholder consultations, more than on the product of the scenarios or models used to produce them. Outlined is the justification, objectives and components of the method. Issues related to stakeholder analysis, elicitation of the future and construction of a model for producing future scenarios are discussed